Representation of Culture in English Textbook: A Content Investigation - Pulungan, Anni Holila; Kusmanto, Joko; Mukmin, Mohammad Jamil bin (Linguists : Journal of Linguistics and Language Teaching, 2024)
Investigation of the usage of English language textbooks in educational institutions has been lacking, despite significant progress and changes on a global scale regarding the cultural dimension of learning English as a global language. This research thoroughly analyzes how culture is portrayed in English textbooks published by the Ministry of Education and Culture, specifically those under the title "Bahasa Inggris-Grade X." The study aims to investigate both the content and how cultural elements are presented within these English textbooks. The study critically examines the contents through descriptive analysis, employing observations and reviewing documents in data analysis. The study discovered that the English textbook contained various cultural categories and interpretations. Out of the total content, 64% related to the source culture, 9% to target culture, 13% to international culture, and 14% represented global culture. When examining the different dimensions of senses, it was encountered that pragmatics was the most dominant, making up 44%, followed by sociological senses at 25%, semantic senses at 19%, while aesthetics had the lowest representation at just 12%. Teachers are encouraged to integrate an English textbook that encompassing a more diverse range of cultural elements assisting learners in broadening their perspectives and emotions to involve them in communities influenced by various of cultural backgrounds actively.